Increase in life expectancy and population growth in Brazil with impact on the number of people living with chronic-degenerative diseases: challenges for the management of Alzheimer's Disease (Research, Society and Development, 2023)
Alzheimer's Disease (AD) and other dementias are chronic neurodegenerative diseases that reach a higher incidence in the older population, and these non-communicable chronic diseases may reach alarming numbers with the growth of the Brazilian population and the increase in life expectancy, since over the last decades the exponential increase in the incidence of non-communicable chronic diseases, such as AD, has been an inexorable phenomenon during the epidemiological transition experienced in the country. In fact, this demographic transition has been considered in theories of health actions in the country, however, little has been effectively done in practice, so that there are still various gaps in policies and actions in the field of public health that are aimed at meeting the needs of the population, local epidemiological needs regarding the attention focused on a complex health care network that can reach the most vulnerable elderly populations impacted by non-communicable chronic diseases, since a possible increase implies an increase in the demand for services and these services must be of quality, aiming at the success in the management of patients, the reduction of morbidity and mortality and the implementation of quality of life and a healthier aging for the patient with an associated decrease in disability-adjusted life years (DALY). In this systematic review we analyze the current case of AD in the Brazilian population, focusing on aspects related to the impacts of the demographic transition on the number of people living with this disease.